Transformation of Model of Relations between Authorities and Media of Rostov Region in 1985—1991 - Ia. S. Evdokimov; V. V. Naukhatsky (Научный диалог)
The prerequisites for the formation of a modern model of relations between regional authorities and print media in the Rostov region, as well as the process of evolution of these relations from 1985 to 1991 is discussed in the article. The author singled out two characteristic stages, carried out their study, revealed characteristics and features. The results of a comparative analysis are presented on a number of fundamental parameters, such as the degree of independence of editorial teams in choosing an information agenda, administrative and legislative control by the party leadership. Particular attention is paid to the historical context, as well as the peculiarities of the development of the media institution itself. The novelty of the study is seen in the fact that a comprehensive study of the relationship between regional authorities and the print media on the materials of the Rostov region has not been previously carried out, a number of previously unpublished archival documents have been introduced into scientific circulation. It has been established that by 1991, horizontal ties had arisen and strengthened in the Don media, new approaches to interaction with state authorities began to take shape. A new generation of professional journalists who were actively involved in politics (they were elected to representative bodies of power at various levels), the development of commercial advertising began.